Large inflammatory fibroid polyp of cardia managed laparoscopically – a case report and review of the literature - Kwiatkowski, Andrzej P. (Wideochir Inne Tech Maloinwazyjne, 2014)
Inflammatory fibroid polyp or Vanek's tumor of the gastrointestinal tract is a rare, benign neoplasm. The lesion may occur at any age but is commonest in the sixth and seventh decades and is more often found in women. It is mostly situated in the stomach, especially in the antrum. Symptoms depend on the location and the size of the lesion. We present a case of a 67-year-old woman with a large inflammatory polyp of the cardia with a diameter of 10 cm × 5.5 cm × 7.5 cm imitating gastrointestinal stromal tumor (GIST). The patient complained of abdominal pain, nausea and mild anemia. We performed laparoscopic topical excision of the tumor. The postoperative course was uneventful. The 6-month follow-up did not reveal recurrence. The clinical image of a large Vanek's tumor can imitate symptoms of gastric cancer or GIST. Topical laparoscopic excision with a 1–2 cm healthy wall margin is a sufficient and adequate way of treatment.